2021
DOI: 10.1097/ceh.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Environmental Scan of Knowledge Brokers Training

Abstract: Introduction: Knowledge brokers (KBs) can promote the uptake of best practice guidelines in rehabilitation. Although many institutions offer training opportunities to health care professionals who wish to undertake KBs roles, the characteristics and content of those educational training opportunities (ETOs) are currently unknown. This study aimed to describe the ETOs available to rehabilitation professionals in Canada and determine whether the ETOs meet the competencies expected of the KBs roles. Methods: We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…Capacity building as conducted by a KB makes the role distinctly different from most local opinion leaders17 or champions18 where the capacity building activities may not occur or may be conducted by another member of the research or implementation team. The importance of the capacity builder role was highlighted in a recent Canada-wide environmental scan of KB training which found that training primarily focuses on preparing people to perform the capacity builder role 38. KBs also acted as knowledge managers in 15 of the 16 included studies, using their understanding of the local context to improve processes and practices to facilitate guideline implementation in a similar fashion to stewardship programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Capacity building as conducted by a KB makes the role distinctly different from most local opinion leaders17 or champions18 where the capacity building activities may not occur or may be conducted by another member of the research or implementation team. The importance of the capacity builder role was highlighted in a recent Canada-wide environmental scan of KB training which found that training primarily focuses on preparing people to perform the capacity builder role 38. KBs also acted as knowledge managers in 15 of the 16 included studies, using their understanding of the local context to improve processes and practices to facilitate guideline implementation in a similar fashion to stewardship programmes.…”
Section: Discussionmentioning
confidence: 99%
“…48,89,94,95 This suggests that KBs success does not only lie in what they do but also in who they are. 96 Despite the availability of a wide range of training programs across Canadian provinces, 97 our findings suggest a lack of awareness of existing KBs-related training opportunities. Consequently, most KBs depended on self-directed learning and on-the-job learning.…”
Section: Characteristics Of Individualsmentioning
confidence: 73%
“…Our search methods were guided by previous research on competencies for public health and continuing education. 16 , 17 Following the steps outlined by Bengtsson 18 and Krippendorff, 19 we analysed the content of all the professional development opportunities identified in the scan to determine their nature and the degree to which they support the development of public health communication competency.…”
Section: Methodsmentioning
confidence: 99%